The Diversity And Abundance Of Leafaud Planthopper (Auchenorrhyncha: Hemiptera) Along With Weeds In Rice Field Ecosystem In South Rantau Of Labuhan Batu Regency - Nirwana Fajri Harahap (JBIO: jurnal biosains (the journal of biosciences), 2015)
The aim of this research is to find out the diversity, abundance, and dominance of leafaud planthopper (Auchenorrhyncha: Hemiptera) along with the types of weeds grow in rice field ecosystem in South Rantau of Labuhan Batu regency. This research was conducted by using purposive random sampling by using insect net. The collection of hopper was done by swinging the insect net for 50 times that took place in north, south, middle, east and south so that the amount of the sampling was 250 swings. The result of this research showed that there were 6 types of rice pests in vegetation period until stublade field in south Rantau of Labuhan Batu regency. They were : Nilaparvata lugens, Nephotettix sp, Cofana spectra, Recilia dorsalis, Thaia sp, Cicadulina bipunctata. The highest abundance was found in Nilaparvata lugens with 407 individuals, Nephotettix sp with 32 individuals, Cofana spectra with 38 individuals, Recilia dorsalis with 26 individuals, Thaia sp with 19 individuals,  and Cicadulina bipunctata with only 1 individual, with low diversity index, it was 0,1075. While the weeds found in south Rantau of Labuhan Batu regency were 5 types, they were Cyperus iria ,Cyperus rotundus,Papalum distichum, Alternanthera philoxeroides, Cyperus pilosus. The highest density was found in Cyperus iria weed, with total 25%, whilw the lowest density was found in Papalum distichum with total only 10%. The highest presence frequency was found in Cyperus iria, Cyperus rotundus, Papalum distichum,  Alternanthera philoxeroides with total 20%, while the lowest presence frequency was found in Cyperus pilosus with total 16%. The highest dominance was found in Cyperus rotundus with total 23.34%, while the lowest dominance was found in Cyperus pilosus with total 15.83%, and the highest important value index was found in Cyperus rotundus with total 64.24%, while the lowest important value index was found in Papalum distichum with total 52.69%. Keywords : Diversity, abundance, dominance, leafaud planthopper